N-Hydroxyphthalimide catalysts as bioactive pro-oxidants. Issue 26 (23rd February 2016) - Melone, L.; Tarsini, P.; Candiani, G.; Punta, C.
Abstract : N -Hydroxyphthalimide organocatalysts bearing lipophilic moieties exhibit a cytotoxic action by promoting oxidative stress in cells. Abstract : The catalytic role of N -hydroxyphthalimide (NHPI) in promoting free-radical hydrogen atom transfer (HAT) reactions, well-documented for processes of industrial and synthetic interest, is here investigated for the first time in a biological environment. While NHPI by itself did not show any bioactivity, selected NHPI-derivatives (NHPIDs) revealed the ability to activate the intracellular formation of reactive oxygen species (ROS), causing the depletion of glutathione (GSH) levels and an increase in oxidative stress (OS). The evident bioactivity of some of these derivatives resulted in a significant reduction of the viability in osteosarcoma MG-63, suggesting a new, potential role of NHPIDs as pro-oxidant drugs. The key role of the N–OH group in promoting oxidative stress is demonstrated.